Investigation of the COMT Val158Met variant association with age of onset of psychosis, adjusting for cannabis use. Issue 11 (6th October 2017) - Lodhi, Rohit J.; Wang, Yabing; Rossolatos, David; MacIntyre, Georgina; Bowker, Alexandra; Crocker, Candice; Ren, Hongyan; Dimitrijevic, Aleksandra; Bugbee, Darren A.; Loverock, Alexandra; Majeau, Brett; Sivapalan, Sudhakar; et al.
Abstract: Objective: COMT rs4680 (Val158Met) genotype moderates the effect of cannabis on the age of onset of psychosis (AoP). We investigated the association between rs4680 and AoP, after adjusting for relevant covariates, in a Canadian Caucasian sample. Methods: One hundred and sixty‐nine subjects with psychosis were recruited. AoP, defined as age of DSM‐IV diagnosis was established using the Structured Clinical Interview for DSM‐IV. Cannabis use data were collected using a self‐report computerized questionnaire. DNA was extracted from saliva and genotyping of the COMT Val158Met polymorphism was done by SNaPshot and TaqMan assays. Logistic regression and Kaplan–Meier analysis results are reported. Results: In those who had used cannabis before 20 years of age, rs4680 had a trend level effect on AoP (median AoP: Val/Val < Val/Met < Met/Met 19.37, 20.95, 21.24 years, respectively; log‐rank test p = .051). Conclusion: Our data are indicative of the need to further investigate the association between the COMT rs4680 variant and AoP in the context of adolescent cannabis use. Abstract : We investigated the association between the COMT Val158Met variant and age of onset of psychosis (AoP), adjusting for cannabis use in 169 Canadian Caucasians. We observed that the COMT Val158Met variant may influence AoP but only in those who had used cannabis before age 20 years.